Osteogenesis imperfecta and potential therapies - Mateusz Fabis; Klaudia Remjasz; Julia Kuchnicka; Wojciech Siedlecki; Jakub Aleksandrowicz; Bartłomiej Wójcik; Karolina Zadrożna (Kazimierz Wielki University, 2022)
Background: Osteogenesis imperfecta (OI) is a genetically determined disorder of connective tissue. In this article we reviewed epidemiology, types of OI, pathophysiology, symptoms and potential therapies. Material and methods: This paper was based on medical articles collected in PubMed from 2006 to 2022, medical websites and books. The research has been done by looking through key words such as: "osteogenesis imperfecta", "osteogenesis imperfecta treatment", "bisphosphonate", "sillence classification". Results: The pathophysiology of osteogenesis imperfecta is well understood. Treatment and symptoms of the disease depend on the type of osteogenesis imperfecta. Conclusions: Treatment of the patients with OI is challenging for health care professionals. Medical care for majority of patients with OI extends their life and improves its quality. Despite advances in science, causal treatment still does not exist.